Drivers of the geographical distribution of nematode-based indices across Europe - Mani, Doina Thais Constance; Mulder, Vera Leatitia; Vazquez Martin, Carmen; Geisen, Stefan; Campos-Herrera, Raquel; Čerevková, Andrea; Cesarz, Simone; Ciobanu, Marcel; Costa, Sofia R.; de Goede, Ron; Eisenhauer, Nico; Jackson, Louise; et al. (Elsevier, 2025)
Nematode-based indices (NBIs) are widely used as indicators of soil health, reflecting key aspects of soil functioning. However, their spatial variability at the European scale remains poorly understood, limiting their integration into soil health policies. This study examines the geographical distribution of the Structure Index and Enrichment Index across seven European environmental zones, identifies the soil-forming factors shaping these patterns, and assesses whether these relationships vary across zones. For this purpose, a pan-European nematode dataset was assembled spanning arable land, agricultural grasslands, natural grasslands, and forests. Structural equation modelling was applied to assess the role of the soil-forming factors: climate, topography, parent material and organisms, as well as indicators of disturbance: extreme weather events and land use intensity. Our findings reveal clear variation in both indices across environmental zones. For the Structure Index, land use effects overrode natural environmental variability, while the Enrichment Index showed increased variability in arable systems. While all soil-forming factors showed relationships with the NBIs, model performance was low. This suggests that key factors were missing, however, disturbance factors did emerge as a key driver. Additionally, the relationship between NBI and environmental drivers varied substantially across zones, emphasizing the need for region-specific approaches. These results highlight the importance of accounting for biogeographical context when interpreting NBIs as indicators for soil health. To enable their effective integration into soil health assessment and policy, future efforts should focus on harmonized sampling, improved data coverage, and the inclusion of ecologically relevant drivers, especially those capturing disturbance.
Keywords: soil health indicators; biogeography; structural equation modelling; soil-forming factors; land use intensity; extreme weather events